Focus. Focus on the Word - Khodjaeva, D.; Tukhtasinova, O. (European Journal of Life Safety and Stability (2660-9630), 2022)
This article discusses emphasis, emphasis on the early stages of the development of Turkic languages, theories of the nature and character of emphasis in modern Turkic linguistics, the study of emphasis in Turkic languages, emphasis on words.